Case report: Clearance of longstanding, immune-deficiency-associated, vaccine-derived polio virus infection following remdesivir therapy for chronic SARS-CoV-2 infection - Bermingham, William Hywel; Canning, Benjamin; Wilton, Thomas; Kidd, Michael; Klapsa, Dimitra; Majumdar, Manasi; Sooriyakumar, Kavitha; Martin, Javier; Huissoon, Aarnoud P. (Frontiers in Immunology, 2023)
The global polio eradication campaign has had remarkable success in reducing wild-type polio (WTP) virus infections (1). This success has largely been built on the use of the live attenuated Sabin oral polio virus (OPV) which has been in widespread use since 1962, although this has been superseded by the use of an inactivated virus in much of the world. The OPV has resulted in a dramatic reduction in wild type polio cases, but the live virus is rarely associated with vaccine-associated paralytic poliomyelitis, particularly in the immunocompromised. The vaccine strains can revert to a neurovirulent type following replication in humans. With wild type infections now suppressed throughout much of the world, vaccine-derived poliovirus (VDPV) infections present a significant challenge to the WHO global polio eradication initiative (2). VDPV have significant sequence divergence compared to the parent strain (>1% sequence divergence (PV1 and PV3) or >0.6% (PV2) in the VP1 gene). Detection of these divergent strains implies many months of ongoing viral replication. This may arise either in the context of prolonged spread in settings of low population immunity or with persistent infection in an immunocompromised individual. VDPV detected due to ongoing community spread is termed circulating VDPV (cVDPV), whilst VDPV from persistent infection in immunodeficient hosts is termed immunodeficiency-associated VDPD (iVDPV) (2). Patients with iVDPV are predominantly reported in those with severe combined immune deficiency or hypogammaglobulinaemia (3). These cases are rare, but significant, with 149 cases reported between 1961-2019 (3). iVDPV infections are, by definition, persistent for >6 months, may demonstrate highly virulent and antigenically modified virus and can cause paralytic illness (3, 4).. It is recognised that such patients have the potential to cause wider outbreaks of iVDPV, but, to date, no data exists to quantify this risk and there is no agreed global strategy to manage these patients (1,4). Here we report, to our knowledge, the first case of resolution of longstanding iVDPV infection in an individual with common variable immune deficiency (CVID, a primary antibody deficiency) following a prolonged, moderate SARS-COV-2 infection where the patient received a total of 12 days of treatment with remdesivir.